2018
DOI: 10.1080/21645515.2018.1452576
|View full text |Cite
|
Sign up to set email alerts
|

Late onset of injection site reactions after vaccination with the 13-valent pneumococcal conjugate vaccine in adult study populations

Abstract: Injection site reactions (ISRs; redness, swelling and pain) commonly occur within 1–2 days after vaccination. After administration of toxoid vaccines including diphtheria toxoid, a later onset of ISRs has also been observed. As the serotype capsular polysaccharides in the 13-valent pneumococcal conjugate vaccine (PCV13) are conjugated to cross-reactive material 197 (CRM197), a nontoxic variant of diphtheria toxin, the onset of ISRs over 14 days was explored in 8 adult studies with 19 cohorts. Subjects received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Previous studies have reported similar findings regarding late-onset solicited local AEs with other vaccines, including diphtheria, tetanus, and pertussis toxoid 34 . The cause of this is likely to be multifactorial, with age being a contributing factor, and warrants further investigation into the pathophysiology 34 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies have reported similar findings regarding late-onset solicited local AEs with other vaccines, including diphtheria, tetanus, and pertussis toxoid 34 . The cause of this is likely to be multifactorial, with age being a contributing factor, and warrants further investigation into the pathophysiology 34 .…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have reported similar findings regarding late-onset solicited local AEs with other vaccines, including diphtheria, tetanus, and pertussis toxoid 34 . The cause of this is likely to be multifactorial, with age being a contributing factor, and warrants further investigation into the pathophysiology 34 . Importantly, this analysis examined the safety, reactogenicity, and immunogenicity of ExPEC10V specifically in participants with a documented history of UTI, an identified risk factor for IED 4 .…”
Section: Discussionsupporting
confidence: 72%
“…As shown in Table 4 , MenACWY-TT was well tolerated in all age groups studied, with its reactogenicity being comparable to that of licensed meningococcal vaccines (the sole exception being higher rates of local reactions seen with MenACWY-TT versus MPSV4, which may be a function of differences in reactogenicity between toxoid conjugated versus nonconjugated vaccines 88 , 89 and routes of administration, with MPSV4 being administered subcutaneously instead of intramuscularly). No safety concerns were apparent whether MenACWY-TT was administered alone or concomitantly with routine licensed vaccines (Tdap or HPV4).…”
Section: Resultsmentioning
confidence: 88%
“…Adults ≥56 years of age who received MenACYW-TT reported higher rates of injection site reactions (pain, erythema, and swelling) of any grade and systemic reactions (fever, headache, malaise, and myalgia) of any grade compared with those receiving MPSV4 [66,67]. The different chemistries of the two vaccines (conjugated in the case of MenACYW-TT and nonconjugated in the case of MPSV4) may account for the differences in reactogenicity, a notion supported by the reported higher incidence of injection site reactions in adults ≥65 years of age receiving a conjugate pneumococcal vaccine compared with those receiving an non-conjugated pneumococcal vaccine [84]. The high content of all 4 serogroup antigens and the carrier protein in MenACYW-TT compared with MCV4-TT did not result in higher reactogenicity.…”
Section: Summary Of Safetymentioning
confidence: 99%